An Analysis of the Relationship Between Body Mass Index (BMI) and Knee Pain in Patients at RSUD Cempaka Putih with an Islamic Perspective Review - Jihan Nabilah; Edi Prasetyo; Karimulloh Karimulloh (Universitas Ibn Khaldun Bogor, 2026)
This study aimed to describe and examine the relationship between Body Mass Index (BMI) and knee pain among adult patients at RSUD Cempaka Putih and to review this relationship from an Islamic perspective. This study employed a quantitative observational analytic design with a cross-sectional approach. The sample consisted of 40 adult patients experiencing knee pain who met the inclusion criteria and were selected using a simple random sampling technique. Data were collected through anthropometric measurements to determine Body Mass Index (BMI) and assessment of knee pain intensity using the Numeric Rating Scale (NRS). Data analysis included univariate analysis to describe the distribution of BMI and knee pain levels, as well as bivariate analysis using the Chi-Square test to assess the relationship between BMI and knee pain. The results showed that the majority of participants had a BMI above the normal range, with more than half of the participants classified as overweight, obese, or obese class II. Knee pain intensity was predominantly moderate to severe. The Chi-Square test indicated that there was no statistically significant relationship between Body Mass Index (BMI) and knee pain severity (p = 0.346). However, descriptively, a tendency toward a higher proportion of severe knee pain was observed among participants with higher BMI, particularly in the obesity and obesity class II categories. There was no statistically significant association between Body Mass Index (BMI) and knee pain among adult patients at RSUD Cempaka Putih.